Different forms of childhood maltreatment have different impacts on the neural systems involved in the representation of reinforcement value. (February 2022) - Blair, Karina S.; Aloi, Joseph; Bashford-Largo, Johannah; Zhang, Ru; Elowsky, Jaimie; Lukoff, Jennie; Vogel, Steven; Carollo, Erin; Schwartz, Amanda; Pope, Kayla; Bajaj, Sahil; Tottenham, Nim; et al.
Abstract: Background: The current study aimed to address two gaps in the literature on child maltreatment, reinforcement processing and psychopathology. First, the extent to which compromised reinforcement processing might be particularly associated with either neglect or abuse. Second, the extent to which maltreatment-related compromised reinforcement processing might be associated with particular symptom sets (depression, conduct problems, anxiety) or symptomatology more generally. Methods: A sample of adolescents (N = 142) aged between 14 and 18 years with varying levels of prior maltreatment participated in this fMRI study. They were scanned while performing a passive avoidance learning task, where the participant learns to respond to stimuli that engender reward and avoid responding to stimuli that engender punishment. Maltreatment (abuse and neglect) levels were assessed with the Childhood Trauma Questionnaire (CTQ). Results: We found that: (i) level of neglect, but not abuse, was negatively associated with differential BOLD responses to reward-punishment within the striatum and medial frontal cortex; and (ii) differential reward-punishment responses within these neglect-associated regions were particularly negatively associated with level of conduct problems. Conclusion: Our findings demonstrate the adverse neurodevelopmental impact of childhood maltreatment, particularly neglect, on reinforcement processing. Moreover, they suggest a neurodevelopmental route by which neglect might increase the risk for conduct problems.